Studi Komparasi Motivasi Belajar dan Konsentrasi Belajar Antara Siswa di Solihuddin School Mathayom 1 Thailand dan Ibnu Aqil Kelas 7 Indonesia - Qory Berliani Elfareta; Rusdi Kasman; Noneng Siti Rosidah (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to compare the learning motivation and concentration of students at Mathayom 1 Solihuddin School Thailand with seventh grade students at Ibnu Aqil Indonesia. The study used a quantitative approach with a comparative design. The study population was 422 students with a sample of 134 students, consisting of 63 students at Solihuddin School Thailand and 71 students at Ibnu Aqil Indonesia who were selected using a simple random sampling technique based on the Slovin formula. Data were collected through a learning motivation and concentration questionnaire that had met the validity and reliability tests, then analyzed using descriptive statistics and an Independent Sample t-test with the help of SPSS 26.0. The results showed that the learning motivation and concentration of students in both schools were in the low category, although there were statistically significant differences between the two groups. This finding indicates that differences in the educational context and learning environment in the two schools have not been able to produce optimal levels of learning motivation and concentration. The low motivation and concentration in both groups indicate that supporting factors for learning, both originating from the school environment, the learning process, and student characteristics, still need attention. This research has implications for the importance of developing more innovative learning strategies, a conducive learning environment, and strengthening teacher and school support to increase student motivation and concentration in learning in both educational contexts.